A systematic review of metakaolin-based alkali-activated and geopolymer concrete: A step toward green concrete - Qader Diyar N.; Jamil Ary Shehab; Bahrami Alireza; Ali Mujahid; Arunachalam Krishna Prakash (Reviews on Advanced Materials Science, 2025)
Expanding the world’s infrastructure drives up demand for building materials, particularly ordinary Portland cement (OPC) concrete, whose high carbon dioxide (CO2) emissions have a detrimental effect on the environment. To address this issue, researchers looked into employing alternative supplementary cementitious materials (SCMs), including metakaolin (MK), which is derived from calcined kaolin clay with pozzolanic properties, to partially or completely replace OPC in concrete. This review article examines the MK’s application in alkali-activated materials (AAMs) and OPC-based concrete. By interacting with calcium hydroxide, MK functions as a pozzolanic additive for OPC concrete, enhancing its mechanical qualities and durability. The use of MK as a source material in AAMs, a newly developed class of sustainable binders, is also covered in this article. The effects of different combinations of MK with additional SCMs, including fly ash (FA), ground granulated blast furnace slag (GGBFS), silica fume, and rice husk ash, on the characteristics of alkali-activated concrete both in its fresh and hardened states, are compiled. The majority of the articles considered in this study are from the past decade, while some relevant articles from 2014 and earlier are also taken into account. The results showed that adding MK to concrete in combination with FA or GGBFS has excellent synergistic effects on microstructural development, pozzolanic activity, and strength increases. In particular, the MK–FA mix demonstrated the most encouraging performance gains. Because of its large surface area, the use of nano-MK helped achieve a denser geopolymer structure and improve mechanical properties. The best curing temperatures for MK-based geopolymers to gain strength were found to be between 40 and 80°C for a total of 28 days. The review also pointed out that the compressive strength and geopolymerization process of MK-based geopolymers were enhanced by increasing the mass ratio of Na2SiO3 to NaOH and NaOH concentration. Nevertheless, geopolymerization was hampered by unnecessarily high alkali concentrations. Moreover, the compressive strength was increased by partially replacing MK with TiO2 or GGBFS. The synergistic effects of combining MK with other SCMs to improve concrete performance highlight the potential of MK-based solutions in lowering the environmental footprint of concrete buildings.